Effect of Light Intensity on Growth and Primary Metabolites Content of Navicula sp. - Mudrikah, Siti; Putri, Renata Adaranyssa Egistha; Kurnianto, Dedy; Rasdi, Abdurrahman Muhammad Fikri; Tia, Erfianti; Suyono, Eko Agus (Universitas Negeri Semarang, 2024)
Global energy demand is steadily rising, necessitating the exploration of sustainable alternatives. Microalgae, such as Navicula sp., offer a promising solution. This study investigated the impact of light intensity on the growth, and biochemical composition (carbohydrates, lipids, proteins, and carotenoids) of Navicula sp. Cultures were grown in f/2 medium under four light intensity treatments: 2100 lux (control), 3500 lux, 4500 lux, and 5500 lux. Cell growth was measured through optical density analysis. Carbohydrate, lipid, protein, and carotenoid assays were performed using phenol-sulfuric acid, Bligh and Dyer, Bradford, and spectrophotometric methods. Maximum growth was observed on the eighth day of cultivation at 4500 lux light intensity. The best specific growth rate was achieved at 5500 lux. The highest biomass, carbohydrate, lipid, and protein productivity were attained at 5500 lux (24.65 mg/mL, 0.374 mg/mL/day, 0.399±0.204 mg/mL/day, and 0.025±0.018 mg/mL/day). Conversely, the highest carotenoid productivity was recorded at 2100 lux, 0.278±0.085 mg/mL/day. By those means, the increase in light intensity was positively correlated with microalgal cell growth, biomass, carbohydrate content, and carbohydrate, lipid, and protein productivity. However, a negative correlation was found with carotenoid pigment productivity. From this research, it is evident that a light intensity of 5500 lux offers a feasible option for the industrial-scale cultivation of Navicula sp. microalgae for biomass, carbohydrate, and protein production, while 2100 lux is more suitable for carotenoid production. This research compares the findings to previous studies, emphasizing the unique way Navicula sp. responds to different light levels.